Plasmonic nano-necklace arrays via reconstruction of diblock copolymer inverse micelle nanotemplates - Lee, Ji Yong; Lee, Jieun; Jang, Yu Jin; Lee, Juyon; Jang, Yoon Hee; Kochuveedu, Saji Thomas; Lee, Sang Soo; Kim, Dong Ha (ROYAL SOC CHEMISTRY, 2011)
We present a facile strategy for the generation of plasmonic nano-necklace arrays by introducing metallic precursors into strings of reconstructed inverse micelle nanotemplates which are induced by applying sequential selective solvent treatment and solvent vapour annealing for quasi-hexagonal arrays of poly(styrene-block-2-vinyl pyridine) inverse micelles.
Keywords: METAL NANOPARTICLES; SURFACE-PLASMONS; PATTERNS; SHAPE; GOLD